The Lord's Prayer as a Model of Prayer; A Hermeneutical Study of Matthew 6:5–15 - Karundeng, Karli Williams; Tewu, Peggy Sandra (Abdurrauf Science and Society, 2025)
This paper is a hermeneutic study of the prayer taught by Jesus to His disciples based on the Gospel of Matthew 6:5-15. The main question in this study is how was the model of prayer taught by Jesus to his disciples? According to Matthew, this prayer formula was given by Jesus on His own initiative after He criticized the wrong understanding and practice of prayer among Judaism. This study uses a descriptive qualitative approach, where the data obtained is in the form of explanations of concepts or texts and not numbers. These data were obtained from literature studies, especially through exegetical studies of Bible manuscripts. The analysis concludes that Jesus provided a new paradigm of prayer through the Lord's Prayer as a model of prayer for His disciples. The prayer model includes several essential elements, starting from the prayer address, worship, petition and doxology. The end of this study is a conclusion about how God's servants should follow the way of prayer taught by Jesus, especially the simple but clear and concise prayer pattern, which consists of the prayer address, worship, petition and doxology.